Functional Characterization of TaFUSCA3, a B3-Superfamily Transcription Factor Gene in the Wheat - Sun, Fusheng; Liu, Xiyan; Wei, Qiuhui; Liu, Jiannan; Yang, Tianxiang; Jia, Liyang; Wang, Yuesheng; Yang, Guangxiao; He, Guangyuan (Frontiers in Plant Science, 2017)
The end-use quality of wheat, including its unique rheology and viscoelastic properties, is predominantly determined by the composition and concentration of gluten proteins. While, the mechanism regulating expression of the seed storage protein genes and other related genes in wheat remains unclear. In this study, we report on the cloning and functional identification of TaFUSCA3, a B3-superfamily transcription factor gene in wheat. Sequence alignment indicated that wheat and barley FUSCA3 genes are highly conserved. Quantitative reverse-transcription (qRT)-PCR analysis showed that the transcript of TaFUSCA3 was accumulated mostly in the stamens and the endosperms of immature wheat seeds. Yeast-one-hybrid results proved that the full-length TaFUSCA3 and its C-terminal region had transcriptional activities. Yeast-two-hybrid and bimolecular fluorescence complementation assays indicated that TaFUSCA3 could activate the expression of the high molecular weight glutenin subunit gene Glu-1Bx7 and interact with the seed-specific bZIP protein TaSPA. DNA-protein-interaction enzyme-linked immunosorbent assay demonstrated that TaFUSCA3 specifically recognizes the RY-box of the Glu-1Bx7 promoter region. Transient expression results showed that TaFUSCA3 could trans-activate the Glu-1Bx7 promoter, which contains eight RY-box sequences. TaFUSCA3 was unable to activate the downstream transcription when the RY-box was fully mutated. TaFUSCA3 could activate the transcription of the At2S3 gene promoter in a complementation of loss-of-function experiment using the Arabidopsis thaliana line fus3-3, which is a FUSCA3 mutant, demonstrating the evolutionary conservation of the TaFUSCA3 gene. In conclusion, the wheat B3-type transcription factor, TaFUSCA3, is functional conserved between monocot and dicocot, and could regulate seed storage protein gene expression by interacting speficically with TaSPA.